In vitro multiplication of strawberry in various types and concentrations of cytokinins and auxins - Suminar, Erni; Rahmawati, Vira; Sumadi, Sumadi; Nuraini, Anne (Kultivasi, 2024)
Growth regulator is one of the important factors in the success of plant propagation by tissue culture. 6-Benzylaminopurine (BAP) is one of the most widely used cytokinin because it is more stable, less expensive and more effective. Thidiazuron (TDZ) can increase the action of other cytokinins, either exogenous cytokinin or endogenous cytokinin. 1-Naphthaleneacetic acid (NAA) belongs to the more stable auxin group, because it is not easily decomposed and oxidized by enzymes released by plants. This study aimed to obtain the best types and concentrations of BAP, TDZ, and NAA for the in vitro multiplication of strawberry explant. The experiment was conducted at the Seed Technology and Tissue Culture Laboratory, Faculty of Agriculture, Universitas Padjadjaran, from April to July 2022. The explants used were axillary shoots of strawberry var. Sweet Charlie is derived from plantlets that were propagated in vitro. The experimental design used was a completely randomized design with six treatments and four replications. The media used were Murashige dan Skoog (MS) with the addition of plant growth regulators (PGRs) in the form of BAP (0 ppm and 0,5 ppm), TDZ (0 ppm and 0,1 ppm), and NAA (0 ppm and 0,1 ppm). The application of different types and concentrations of BAP, TDZ, and NAA resulted in different effects of in vitro shoot multiplication of strawberry explant var. Sweet Charlie. Concentration of 0.1 ppm TDZ produced the highest number of shoots (5.38).